A case of multiple cutaneous schwannomas; schwannomatosis or neurofibromatosis type 2?. Issue 2 (17th January 2006) - Murray, A J; Hughes, T A T; Neal, J W; Howard, E; Evans, D G R; Harper, P S
Abstract : A 54 year old man presented with numerous cutaneous schwannomas, cranial nerve lesions, and spinal cord lesions, but no evidence of vestibular nerve involvement. There was no family history of neurocutaneous lesions. To help discriminate between the various possible diagnoses in this patient, molecular analysis of two cutaneous schwannomas was undertaken. An identical point mutation in the NF2 gene in the two anatomically distinct tumours was found, confirming this as a case of NF2 mosaicism.